Differential expression of MicroRNA let-7e and 296-5p in plasma of Egyptian patients with essential hypertension - Heba K. Badawy; Dina M. Abo-Elmatty; Noha M. Mesbah (Heliyon, 2018)
Essential hypertension is a chronic medical condition affecting thousands of people worldwide. Hypertension results from interplay of genetic and environmental factors. MicroRNAs regulate gene expression and can be biomarkers for disease. MicroRNA let-7e and microRNA 296-5p have been linked to different cardiovascular diseases. This study aimed to determine association of serum miRNA let-7e and miRNA 296-5p with essential hypertension in Egyptian patients. MicroRNA let-7e and miRNA-296-5p expression was determined in sera of 25 hypertensive patients and 25 normotensive controls by quantitative real-time polymerase chain reaction. Hypertensive patients showed significantly higher expression of miRNA let-7e (3.23-fold increase, p = 0.036) in comparison with normotensive controls. In hypertensive patients, miRNA let-7e expression was positively correlated with increased systolic and diastolic blood pressure. Furthermore, miRNA 296-5p expression was negatively correlated with serum total cholesterol and low-density lipoprotein. Results from this study indicate that miRNA let-7e can potentially be a biomarker for essential hypertension.